Constructions of loneliness in older people in the New Zealand news and current affairs media : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology with endorsement in Health Psychology at Massey University, Manawatū, New Zealand - Bidois, Jolinda Ruth (Massey University, 2017)
Loneliness is a subjective, painful, personal experience and it has negative effects on physical and mental health. The way that loneliness in older people is constructed in the mass media can reflect or influence public perceptions regarding that issue. Analysis of media reports can contribute to understanding how loneliness in older people is understood. This study is based in a social constructionist understanding and investigates the way that loneliness in older people is constructed in the New Zealand news and current affairs media. A discourse analysis was undertaken of articles regarding loneliness in older people, published in New Zealand in 2016 from selected newspapers, magazines, and a news website. Five discourses are described which are utilised in those news and current affairs articles regarding loneliness in older people. They are named the morality, economic, medical, dependence, and relational discourses. Each of these discourses has been identified in previous research. In the first four of these discourses, older people who experience loneliness are commonly offered passive subject positions of reduced power and agency, and loneliness in older people is problematised. Older people quoted in the news and current affairs articles drew on a relational discourse which, in contrast, positioned older people, including those who experienced loneliness, in interdependent relationships. A focus on the voice of older people highlights that they draw on a different discourse from others, and it is a discourse which enables more powerful and agentive subject positions for older people, especially those who experience loneliness.
Keywords: Older people in mass media; Loneliness in old age; Press coverage; New Zealand; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Psychology